(untitled) (Research, Society and Development, 2018)
This work consists of a theoretical analysis that aims to discuss the relationship between federalism and Brazilian educational policies, making a historical course that begins with the Proclamation of the Republic and extends to the current Federal Constitution. It is carried out the literature and documental analysis, which addresses the genesis of federalism, based on the model implemented in the United States, as well as in Brazil, characterized by the alternation between periods of authoritarianism and democratic regime, which reflect greater or less centralization of the political power. It is understood that the process of political-administrative decentralization that originated the 1988 Constitution has made possible the development of a system of collaboration between the Union and other federated entities, responsible for ensuring social rights for citizens, including educational rights.